Korelacija renalnih i metaboličkih biomarkera sa nivoom vitamina D kod žena u postmenopauzi - Klisic, Aleksandra (Journal of Medical Biochemistry, 2023)
Objective: To our knowledge, the mutual involvement of a variety of metabolic and renal biomarkers and vitamin D (determined as 25-hydroxyvitamin D [25(OH)D]) in postmenopausal women has not been examined yet. Therefore, we aimed to explore such a relationship by a thorough statistical multimarker approach.Patients and Methods: A total of 150 (diabetes and cardiovascular disease-free) postmenopausal women were included. Anthropometric and biochemical parameters were measured. The fatty liver index (FLI) and Homeostasis model assessment of insulin resistance (HOMA-IR) were calculated. Univariate and multivariate binary logistic regression analyses were used to test the predictions of cardiometabolic markers for [25(OH)D] status. Principal component analysis (PCA) was applied to explore the effect of examined biomarkers on [25(OH)D] status.Results: Univariate binary regression analysis revealed positive associations between FLI and [25(OH)D] [OR=1.036 (1.020-1.052), P